Control of Networked Systems Containing Multiple Agents - Cruz, Jose B, Jr (Archīum Ateneo, 2010)
: This position paper illustrates the use of a natural framework for the modelling, analysis, and design of engineering systems that involve two or more controllers, each of which has an associated objective function. Such systems arise when ordinary single controller systems are networked through communication links so that the information available to each controller may contain aspects of the other systems’ states and the optimization of each objective function is no longer decoupled from each other. Single controller optimization is no longer directly applicable. Appropriate to the study of such systems is the theory of games that has been developing in mathematics, economics, and engineering for the past 60 years. There are extensive applications in economics, but in engineering the applications are scarce. In recent years, there has been great attention to global problems such as the negative environmental impact of energy use, and global warming. These problems arise from complex systems with multiple controllers. Among the approaches for dealing with the problems, there should be one on a total systems approach with a game theory base. A natural framework for this is the subject of this policy paper.